Main aspects of etiopathogenesis, diagnosis and treatment of subhyaloid hemorrhages - D. O. Shkvorchenko; S. A. Kakunina; K. S. Norman; I. A. Drozdkov; M. R. Obraztsova (Офтальмохирургия, 2021)
Purpose. To present modern literature data on the main aspects of etiopathogenesis, diagnosis and treatment of subhyaloid hemorrhages. Material and methods. To perform the review, the search for literature sources on PubMed abstract databases was analyzed by the keywords «subhyaloid hemorrhages», «posterior hyaloidotomy» according to Russian publications on the topic of the article for the period up to 2020 inclusive. Results. Subhyaloid hemorrhage is a suspension of blood in a space bounded by a mesh membrane and a detached posterior hyaloid membrane. The most common cause of subhyaloid hemorrhages are retinal vascular diseases: diabetic retinopathy of the retina (30%), Valsalva hemorrhagic retinopathy (30%), central retinal vein thrombosis (20%). Subhyaloid hemorrhages are less common in hematological diseases, eye injury, rupture of the macroaneurysm, Terson syndrome. It has been established that the main complications due to untimely or inadequate treatment of subhyaloid hemorrhages are the formation of a premacular fibrous membrane, vitreoretinal fusion, traction retinal detachment, hemophthalmos, fibrosis and retinal atrophy, which require the right tactics in treatment. Conclusion. Thus, due to the prolonged presence of blood and fibrin in the premacular subhyaloidal space, there is a danger of mechanical and toxic effects on the retinal neuroepithelium of the macular region, which can lead to an irreversible decrease in visual functions.